Physical Properties Test of Antiseptic Soap Combination of Honey Pineapple Peel Extract and Squeezed Orange Peel - Inur Tivani Tivani; kusnadi kusnadi kusnadi (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2022)
The pandemic era has an impact on the increase in hand washing soap for the implementation of health protocols. The process of making soap with chemicals for some people who have sensitivity to these ingredients results in dry, rough and itchy skin. The breakthrough that needs to be done is by making soap made from natural ingredients that are safe for the skin and environmentally friendly. Honey pineapple peel and squeezed orange peel contain antibacterial compounds such as flavonoids, tannins and saponins. The purpose of this research is to find out which formula for antiseptic soap combination of these two natural ingredients is the best in terms of physical properties. This research was carried out at the Microbiology Laboratory of the Harapan Bersama Polytechnic. Honey pineapple peel and squeezed orange peel were extracted by maceration method and then 3 formulas were made with 3 replications. The physical properties tested were organoleptic test, pH test, specific gravity test, viscosity test, and preference test. Values that meet the standards of the test are considered antiseptic soaps that meet the physical test standards. The results of this study showed that all antiseptic soap formulas were good from the physical properties test. When viewed from the preference test, antiseptic soap combination of honey pineapple peel extract and squeezed orange peel with a ratio of (3:1) is the best.